The Vues d’optique Prints of the 18th — First Quarter of the 19th Century: From Inscriptions to Dating - Demidenko, Iuliia B. (Actual Problems of Theory and History of Art, 2018)
The inscriptions on the “marginal” kinds of engravings (optical prints, folk woodcuts, fashion prints, etc.) usually include only the title of an engraving, the date, and the authorship, rarely, but at the same time — a lot of other inscriptions: serial numbers, the names of printers and publishers, their addresses, and so on. Despite the seeming insignificance of this information, it can be valuable, allowing to establish, in particular, the date.The optical prints of the 18th — first quarter of the 19th century, a popular type of engravings, only recently has become the subject of special study. They usually do not have any authorship, though they do have prototypes in classical engravings. They are particularly the engravings with views of St. Petersburg made by Russian 18th century engravers after drawings by M. Makhaev. The dating of “video-engravings” is difficult, there are contradictions in the literature”, — noted an expert on “Makhaev’s optic prints”, M. Alexeyeva. With regard to Augsburg and Italian editions, these contradictions can be removed through the research in the Augsburg City Archive and thanks to revealed Remondini publishing house catalogs.The analysis of the inscriptions in the margins can significantly refine the dating of the London and Paris editions of optical prints. English and French printers and publishers often wrote their addresses. From the comparison with address books of the 18th — early 19th centuries it is possible to determine the period of the release of various prints. Some of the publishers pointed out their address on prints, while others put down the names of their ancestors from whom they inherited the printing business. The same can be said about London publishers. In such cases, it is clear that they printed their engravings from the same printing plates; therefore, you can build a certain sequence of publications of certain engravings by different publishers.
Keywords: engravings; Makhaev; prints; Russia; St. Petersburg; vues d’optique